Are mouse models of asthma appropriate for investigating the pathogenesis of airway hyper-responsiveness? - Kumar, Rakesh K.; Foster, Paul S. (Frontiers in Physiology, 2012)
Whether mouse models of chronic asthma can be used to investigate the relationship between airway inflammation/remodelling and airway hyper-responsiveness (AHR) is a vexed question. It raises issues about the extent to which such models replicate key features of the human disease. Here, we review some of the characteristic pathological features of human asthma and their relationship to AHR, and examine some limitations of mouse models that are commonly used to investigate these relationships. We compare these conventional models with our mouse model of chronic asthma involving long-term low-level inhalational challenge, and review studies of the relationship between inflammation/remodelling and AHR in this model and its derivatives, including models of an acute exacerbation of chronic asthma and of the induction phase of childhood asthma. We conclude that while extrapolating from studies in mouse models to AHR in humans requires cautious intepretation, such experimental work can provide significant insights into the pathogenesis of airway responsiveness and its molecular and cellular regulation.